HOW TO DRAW COOL STUFF STROKE BY STROKE - Harris, Jonathan Stephen, freelance artist; Ankner, Florian (Indianapolis, IN Dorling Kindersley Limited, 2021)
Are you tired of drawing the same boring stuff? Artist and author Jonathan Stephen Harris shows you how to draw almost anything with 40 fun and exciting projects that are anything but boring. You'll learn how to create crazy trick art, amazing 3D objects, mind-blowing anamorphic illustrations, and brain-twisting optical illusions. Every project features detailed, step-by-step instructions and illustrations that use color to help teach you exactly how to do it. You'll start by learning the basics of drawing, what tools you need, and the basic techniques you need to know so you can create your own amazing drawings. Soon you'll be creating works of amazing art that is out of this world!
Keywords: Drawing -- Technique; Cookbooks